The value conflict between freedom and security: Explaining the variation of COVID-19 policies in democracies and autocracies. - Nicole J Saam; Carmen Friedrich; Henriette Engelhardt (PLoS ONE, 2022)
In the name of health security, individual freedoms were constrained in an unprecedented way in many countries, democratic or authoritarian, all over the world during the COVID-19 pandemic. Yet the constraints have not been consistent across countries, which motivates this paper to examine the relevance of value preferences towards freedom or security in the society for COVID-19 policies. Based on data for 40 democratic and authoritarian countries, the analyses show that the variation in the stringency of COVID-19 policies can be explained by value preferences of the population only in autocracies. In democracies, however, we do not find such a relationship. Governments in democratic political systems, we argue, are responsive to their constitutions and face prosecution by the judiciary if they violate the law or provisions of the constitution, limiting their capacity to implement strong COVID-19 policies. Nevertheless, their COVID-19 policies restricted citizens' freedoms and liberties, which means that these policies were rather not responsive to citizens' preferences for freedom, democratic rights and liberties. By highlighting how autocracies respond to their citizens' value preferences for security, this paper contributes to a better understanding of how autocracies might gain legitimacy in times of crises.